INTEGRASI SISTEM CONVENYOR DAN LENGAN ROBOT BERBASIS PLC DAN ARDUINO DALAM PROSES PEMINDAHAN BARANG - Luha, Agusto Frendy (Universitas Islam Balitar Blitar, 2024)
Automation systems play a central role in modern industries. The presence of automation within industries holds significant importance in enhancing efficiency throughout production stages. The rapid development of automation technology aims to alleviate human tasks, monitor operational processes, and regulate system performance optimally. In addressing the challenges of complex material handling, automation solutions have been implemented through the utilization of conveyor systems and robotic arms. Conveyors serve as material transport mechanisms, although they possess specific effectiveness, they also encounter operational limitations. On the other hand, robots as automated systems can be controlled through microcontrollers and possess physical capabilities for specific tasks. Within this context, the research involves the design of electronic systems employing PLCs for conveyor control and Arduinos for robotic arm control. Through the integration of conveyors and robotic arms, this prototype development demonstrates significant potential in meeting the demands of industrial automation. Comprehensive test results concerning load lifting capabilities reveal that the robotic arm can efficiently handle loads with a maximum weight of 17 grams. However, factors such as the suboptimal nature of the robotic arm material and limitations in equipment size also contribute to these outcomes.